Wireless Sensor Networks Framework for Indoor Temperature Regulation - Risteska Stojkoska, Biljana; Popovska Avramova, Andrijana (South East European Research Centre, Thessaloniki, Greece, 2013)
Wireless Sensor Networks take a major part in our everyday lives by enhancing systems for home automation, health-care, temperature control, energy consumption monitoring etc. In this paper we focus on a system used for temperature regulation for homes, educational, industrial, commercial premises etc. We propose a framework for indoor regulation and optimization of temperature using wireless sensor networks based on ZigBee. Methods for optimal temperature regulation are suggested and discussed. The framework is based on methods that provide energy savings by reducing the amount of data transmissions through prediction methods. Additionally the framework explores techniques for localization, such that the location of the nodes is used for optimization of the temperature settings. Information on node location is used to provide the most optimal tradeoff between the time it takes to reach the desired temperature at a specific part of the room and energy consumption.
Keywords: temperature optimization, wireless sensor networks, ZigBee